Mechanical, durability and microstructure properties of lightweight concrete using aggregate made from lime-treated sewage sludge and palm oil fuel ash - Lau, P. C.; Teo, DCL; Mohammad, Abdul Mannan (Elsevier Ltd., 2018)
This paper reports the investigation on toxicity characteristics, microstructure, physical and mechanical properties of artificial Posslite lightweight aggregate (LWA) made from lime-treated sewage sludge (SS) and palm oil fuel ash (POFA). The presence of crystals and a dense shell of Posslite LWA enhanced its strength and the rounded shape of LWA enhanced the workability of fresh lightweight aggregate concrete (LWAC). Results showed that mechanical and durability properties of Posslite LWAC were comparable to normal weight aggregate concrete (NWAC). Posslite LWAC possesses compressive strength, VPV, sorptivity, chloride diffusion of 50.4 MPa, 8.7%, 0.0151 mm/s0.5 and 2.12 1011 m2 /s, respectively.